2017
DOI: 10.1177/0897190017734766
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Modes of Mechanical Ventilation: Introduction for the Critical Care Pharmacist

Abstract: Mechanical ventilation continues to be an evolving modality in the critical care environment. Technological advances in microprocessor-controlled ventilation integrated with the complexity of new ventilator modes has provided the multidisciplinary team opportunities to further improve the care of the critically ill ventilator patients. As members of the critical care multidisciplinary team, pharmacists require a basic understanding of both conventional and advanced modes of mechanical ventilation in order to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…In this activity, there is the responsibility of intervention regarding potential drug interactions, dosage adjustments, dilution and reconstitution adjustments, de nition with the nurse and physician of the best time for administration, drug substitution, analysis of the route of administration, always ensuring patient safety 22 . The clinical pharmacist in ICU is also instigated to monitor laboratory test changes, as well as to assist in the care of patients on mechanical ventilation 23 . This professional can also perform discharge orientation, answering questions the patient may have about other drugs that help in treatment and how they should be used at home, after discharge 24,25 , or during transitions from the ICU to other units, or from other units to the ICU 13 .…”
Section: Activities Pertinent To the Hospital Clinical Pharmacist In ...mentioning
confidence: 99%
“…In this activity, there is the responsibility of intervention regarding potential drug interactions, dosage adjustments, dilution and reconstitution adjustments, de nition with the nurse and physician of the best time for administration, drug substitution, analysis of the route of administration, always ensuring patient safety 22 . The clinical pharmacist in ICU is also instigated to monitor laboratory test changes, as well as to assist in the care of patients on mechanical ventilation 23 . This professional can also perform discharge orientation, answering questions the patient may have about other drugs that help in treatment and how they should be used at home, after discharge 24,25 , or during transitions from the ICU to other units, or from other units to the ICU 13 .…”
Section: Activities Pertinent To the Hospital Clinical Pharmacist In ...mentioning
confidence: 99%
“…Mechanical ventilation (MV) is a frequently encountered supportive care modality in critically ill patients. (1) While life-saving, mechanical ventilation predisposes patients to notable sequalae that can adversely affect patient-centered outcomes including ventilator induced lung injury (VILI), infection, intensive care unit (ICU) acquired muscle weakness, etc. that make the decision to intubate, daily evaluation of extubation potential, and need for tracheostomy essential bedside assessments.…”
Section: Introductionmentioning
confidence: 99%
“…); however, mechanical ventilation cannot be viewed as an isolated intervention but is deeply intertwined with a patient’s overall clinical status and associated pharmacotherapy regimen. (1,511) Indeed, associated pharmacotherapy regimens are complex with over 30% of patients in the ICU setting having greater than 20 medications prescribed. (12,13) This same study showed that 70% of patients had more than 13 medications at any given point.…”
Section: Introductionmentioning
confidence: 99%